Does violence in adolescence differentially predict offending patterns in early adulthood? - Cardwell, Stephanie M. (International journal of offender therapy and comparative criminology, 2018)
Previous research is mixed on whether the commission of a violent offense in adolescence is predictive of criminal career characteristics. In the current study, we addressed the following: (a) What factors predict the commission of serious violence in mid-adolescence? and (b) Does involvement in serious violence in mid-adolescence lead to more chronic and/or more heterogeneous patterns of offending in early adulthood? Data were obtained from the Pathways to Desistance Study, a longitudinal study of serious adolescent offenders in Philadelphia, Pennsylvania, and Phoenix, Arizona. Prior arrests, violence exposure, and gang involvement distinguished adolescents who engaged in violence at baseline. A violent offense at baseline was not predictive of a higher frequency of rearrests but was associated with membership in the low offending trajectory. In conclusion, violent offending in adolescence might be a poor predictor of chronic and heterogeneous patterns of offending throughout the life course.